Effect of Hyperbaric Oxygen Therapy on Chronic Wound Healing: A Narrative Review - Atchara Kittima Nooch; Sarocha Ratree Lallita; Thao Duyen Yuan (Journal of Wound Research and Technology, 2024)
Background: Chronic wounds such as leg ulcers are great socioeconomic burdens. Besides, these wounds become very unbearable with hypoxia. Hyperbaric oxygen therapy (HBOT) has emerged as one of the most laudable treatment approaches to this problem and has improved the delivery of oxygen to wounds. Purpose: To review HBOT's effects on chronic wound healing considering its clinical applications, mechanisms of action, and benefits for patient outcomes. Methods: A systematic review and meta-analysis were conducted according to the PRISMA 2020 guidelines. Eight authors independently searched five databases (CINAHL, ProQuest, PubMed, ScienceDirect, and Wiley) for studies published between September 2019 and July 2024. Results: The literature cites that HBOT improves the healing of wounds by improving tissue oxygenation, stimulating the synthesis of collagen, and inducing angiogenesis. The studies show that HBOT reduces healing time, particularly in the case of diabetic wounds, and lowers the rates of amputation and infection. HBOT, mechanistically, mediates tissue repair by modulating reactive oxygen and nitrogen species and boosts vascular endothelial growth factor levels, enhancing graft survival and overall wound healing. Conclusion: HBOT is an excellent adjunct to therapy against chronic wounds that respond poorly to treatment. Better healing outcomes, fewer complications, and better quality of life for chronic wound patients could be accomplished by including this aspect in standardized protocols for wound care.